Transmission of Antibiotic-Resistant Escherichia coli from Chicken Litter to Agricultural Soil - Fatoba, Dorcas Oladayo; Amoako, Daniel Gyamfi; Abia, Akebe Luther King; Essack, Sabiha Yusuf (Frontiers in Environmental Science, 2022)
A growing concern regarding the use of animal manure as fertilizer is the contamination of soil, plants, and the environment with a variety of antibiotic-resistant and pathogenic bacteria. This study quantified and characterized the antibiotic resistance profiles of Escherichia coli in the soil before and after chicken litter application to determine the impact of manure on the soil resistome. Litter and soil samples were collected from a sugarcane field before and after litter application. E. coli was isolated and quantified using the Colilert®-18/ Quanti-tray® 2000, and 10 randomly selected isolates from the positive wells of each Quanti-tray were putatively identified on eosin methylene blue agar. Real-time PCR was used to confirm the isolates by targeting the uidA gene. Antibiotic susceptibility test against 18 antibiotics was conducted using the disk diffusion method, and the multiple antibiotic resistance index (MARI) was calculated. Soil amendment with chicken litter significantly increased the number of antibiotic-resistant E. coli in the soil. Among the 126 E. coli isolates purified from all the samples, 76% showed resistance to at least one antibiotic, of which 54.2% were multidrug-resistant (MDR). The highest percentage resistance was to tetracycline (78.1%), with the least resistance (3.1%) to imipenem, tigecycline, and gentamicin. The isolates also showed resistance to chloramphenicol (63.5%), ampicillin (58.3%), trimethoprim-sulfamethoxazole (39.6%), cefotaxime (30.2%), ceftriaxone (26.0%), cephalexin (20.8%), cefepime (11.5%), amoxicillin-clavulanic acid (11.5%), cefoxitin (10.4%), Nalidixic acid (9.4%), amikacin (6.3%), and ciprofloxacin (4.2%). Of the 54.2% (52/96) MDR isolates, the highest number was isolated from the litter-amended soil (61.5%) and the least isolates from soil samples collected before litter application (1.9%). The relatively higher mean MAR index of the litter-amended soil (0.14), compared to the soil before the amendment (0.04), suggests soil pollution with antibiotic-resistant E. coli from sources of high antibiotic use. E. coli could only be detected in the soil up to 42 days following manure application, making it a suitable short-term indicator. Notwithstanding its relatively short-term detectability/survival, the application of chicken litter appeared to transfer antibiotic-resistant E. coli to the soil, enhancing the soil resistome and highlighting the consequences of such agricultural practices on public health